Evaluation Management in Islamic Religious Education: A Case Study of Hearing-Impaired Students in Indonesia: Manajemen Evaluasi dalam Pendidikan Agama Islam: Studi Kasus Siswa Tunarungu di Indonesia - Slamet Pamuji; Uthman Shehu Lawal (Mapendis: Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the management of evaluation in Islamic Religious Education (IRE) learning for hearing-impaired students at SMPLB Yakut Purwokerto. Evaluation plays a crucial role in determining the achievement of learning objectives, particularly in inclusive education settings that require specific pedagogical and managerial approaches. This research employed a qualitative case study design. Data were collected through in-depth interviews, participant observation, and documentation involving school principals, IRE teachers, and students. The findings reveal that the management of IRE evaluation was implemented through several stages: planning, organizing, implementing, supervising, and follow-up actions. Evaluation planning was adapted to students’ hearing limitations by emphasizing visual and practical assessment techniques. The organization of evaluation involved coordination between teachers and school management. Implementation of evaluation utilized modified written tests, performance-based assessments, and continuous observation. Supervision was conducted through periodic monitoring by school leaders, while follow-up actions included remedial teaching and individualized guidance. This study concludes that effective evaluation management in special education requires flexibility, collaboration, and contextual adaptation to students’ needs. The findings contribute to the development of evaluation management models in Islamic education for students with disabilities.